Serum immunoglobulin G and mucosal immunoglobulin A antibodies from prepandemic samples collected in Kilifi, Kenya, neutralize SARS-CoV-2 in vitro. (February 2023) - Nyagwange, James; Kutima, Bernadette; Mwai, Kennedy; Karanja, Henry K.; Gitonga, John N.; Mugo, Daisy; Sein, Yiakon; Wright, Daniel; Omuoyo, Donwilliams O.; Nyiro, Joyce U.; Tuju, James; Nokes, D. James; et al.
Highlights: SARS-CoV-2 spike reactive serum immunoglobulin G antibodies are present in prepandemic samples. SARS-CoV-2 spike reactive mucosal immunoglobulin A antibodies are present in prepandemic samples. SARS-CoV-2 spike reactive prepandemic antibodies neutralize pseudotyped SARS-CoV-2. Prepandemic antibodies are also cross-reactive to human endemic coronaviruses. Abstract: Objectives: Many regions of Africa have experienced lower COVID-19 morbidity and mortality than Europe. Pre-existing humoral responses to endemic human coronaviruses (HCoV) may cross-protect against SARS-CoV-2. We investigated the neutralizing capacity of SARS-CoV-2 spike reactive and nonreactive immunoglobulin (Ig)G and IgA antibodies in prepandemic samples. Methods: To investigate the presence of pre-existing immunity, we performed enzyme-linked immunosorbent assay using spike antigens from reference SARS-CoV-2, HCoV HKU1, OC43, NL63, and 229E using prepandemic samples from Kilifi in coastal Kenya. In addition, we performed neutralization assays using pseudotyped reference SARS-CoV-2 to determine the functionality of the identified reactive antibodies. Results: We demonstrate the presence of HCoV serum IgG and mucosal IgA antibodies, which cross-react with the SARS-CoV-2 spike. We show pseudotyped reference SARS-CoV-2 neutralization by prepandemic serum, with a mean infective dose 50 of 1: 251, which is 10-fold less than that of the pooled convalescent sera from patients with COVID-19 but still within predicted protection levels. The prepandemic naso-oropharyngeal fluid neutralized pseudo-SARS-CoV-2 at a mean infective dose 50 of 1: 5.9 in the neutralization assay. Conclusion: Our data provide evidence for pre-existing functional humoral responses to SARS-CoV-2 in Kilifi, coastal Kenya and adds to data showing pre-existing immunity for COVID-19 from other regions.